The philosophy of science and human rights in the Colombian legal system: Case study on human dignity - Marín Gil, Johnny (DIXI, 2021)
Theme and scope: This research article delves into the concept of social science as a transforming element of society. It is key a vision from law as a science that regulates the behavior of human beings to improve their living conditions. Characteristics: Society requires more humanization and less cold numbers. Statistics and diagnoses are not agents of change; on the contrary, man is. Findings: The main cornerstone was the demonstration that the philosophy of science can be an option for transformation. Conclusions: A society based on respect for human rights and founded on the dignity of the human being is the path to social justice. Philosophizing, thinking and loving wisdom is an option for evolution. Science can be humanized.